The Copyright Pentalogy: How the Supreme Court of Canada Shook the Foundations of Canadian Copyright Law - MICHAEL GEIST (University of Ottawa Press, 2013)
Copyright cases typically reach the Supreme Court of Canada (the Court) only once every few years, ensuring that each case is carefully parsed and analyzed. On 12 July 2012, the Court issued rulings on five copyright cases in a single day, an unprecedented tally that shook the very foundations of copyright law in Canada. In fact, with the decisions coming just weeks after the Canadian government passed long-awaited copyright reform legislation, Canadian copyright law experienced a seismic shift that will take years to sort out. Not surprisingly, the immediate coverage of the Courtâ€™s decisions, which were quickly dubbed the â€œcopyright pentalogy,â€ focused on the specific outcomes for the litigants, including wins for Bell and computer giant Apple (no fees for song previews on services such as iTunes),1 the entertainment software industry (no additional payment for music included in downloaded video games),2 and the education community (copying materials for instructional purposes may qualify as fair dealing).3 Yet it took little time for the Canadian copyright community to begin to debate the larger implications of the decisions. Several issues quickly came to the fore. First, the cases provided an unequivocal affirmation that copyright exceptions such as fair dealing should be treated as usersâ€™ rights. The Court first raised the notion of balancing creator rights and user rights in 2004. Publisher and creator groups had urged the Court to retreat from its user rights approach, claiming it was merely a metaphor, yet the Court used these cases to re-emphasize the importance of usersâ€™ rights. The user rights analysis affects virtually all copyright cases, forcing all courts to ensure that there is a fair balance between the interests of creators and users. Moreover, the usersâ€™ rights framework has attracted growing attention worldwide, as Canadian copyright law is increasingly cited as the paradigm example for emphasizing both creator and user rights.